Investigation of Blended Learning Components in Medical Education - Morteza Zeighami; Mahmoud Abolghasemi; Gholamreza Sharifi Rad (Iranian Evolutionary Educational Psychology Journal)
Objective: The focus of this article is on blended learning in medical education, including its components and implementation. Methods: The research method used is a descriptive-analytical review, with content sourced from books and articles. The article aims to elucidate the concept of blended learning in medical education through implicit knowledge. The integration of information and communication technology in education has resulted in the adoption of blended learning environments. Results: Blended learning involves utilizing multiple teaching methods, strategies, techniques, or media to deliver educational content and materials. It has been proposed as the second wave of e-learning and is a new approach in educational planning that combines electronic and face-to-face equipment, as well as student-centered and teacher-centered methods. This approach seeks to combine cognitive learning principles and social constructivism, bringing together informative, enabling, and creative education systems. The use of blended learning strengthens learners' activities by incorporating problem-solving and questioning methods through group interactions and healthy competition within a dynamic structure. Conclusions: This study discusses the concepts, foundations, methods, and advantages of blended learning in electronic education. The use of blended learning can promote and expand innovative teaching-learning approaches, particularly in the face of emerging epidemics such as COVID-19.